Spark: A navigational paradigm for genomic data exploration - Nielsen, Cydney B.; Younesy, Hamid; O'Geen, Henriette; Xu, Xiaoqin; Jackson, Andrew R.; Milosavljevic, Aleksandar; Wang, Ting; Costello, Joseph F.; Hirst, Martin; Farnham, Peggy J.; Jones, Steven J.M. (Genome Research, 2012)
Biologists possess the detailed knowledge critical for extracting biological insight from genome-wide data resources, and yet they are increasingly faced with nontrivial computational analysis challenges posed by genome-scale methodologies. To lower this computational barrier, particularly in the early data exploration phases, we have developed an interactive pattern discovery and visualization approach, Spark, designed with epigenomic data in mind. Here we demonstrate Spark's ability to reveal both known and novel epigenetic signatures, including a previously unappreciated binding association between the YY1 transcription factor and the corepressor CTBP2 in human embryonic stem cells.